+0  
 
0
29
1
avatar+135 

How do you do this:

x^-3/2

 
ISmellGood  Sep 13, 2017
social bar
Sort: 

1+0 Answers

 #1
avatar+90127 
+1

How do you do this:

x^-3/2

 

\(\frac{x^{-3}}{2}=\frac{1*x^{-3}}{2}=\frac{1}{2x^{+3}}=\frac{1}{2x^{3}}\\~\\ \text{or maybe you mean}\\~\\ x^{-3/2}=1*x^{-3/2}=\frac{1}{x^{+3/2}}=\frac{1}{x^{3/2}}\\~\\ \text{can also be written as}\\ \frac{1}{x^{3/2}}=\frac{1}{(\sqrt x)^3}=\frac{1}{\sqrt{x^3}}\)

 
Melody  Sep 14, 2017

29 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details